Ant Colony-Inspired Parallel Algorithm to Improve Cryptographic Pseudo Random Number Generators - Keller, Jorg; Spenger, Gabriele; Wendzel, Steffen (2017 IEEE Security and Privacy Workshops (SPW), 2017)
We present a parallel algorithm to compute promising candidate states for modifying the state space of a pseudo-random number generator in order to increase its cycle length. This is important for generators in low-power devices where increase of state space is not an alternative. The runtime of the parallel algorithm is improved by an analogy to ant colony behavior: if two paths meet, the resulting path is followed at accelerated speed just as ants tend to reinforce paths that have been used by other ants. We evaluate our algorithm with simulations and demonstrate high parallel efficiency that makes the algorithm well-suited even for massively parallel systems like GPUs. Furthermore, the accelerated path variant of the algorithm achieves a runtime improvement of up to 4% over the straight-forward implementation.